Efficacy of plant extracts of controlling the lesser grain borer in seed storage - Silawong, Panrada; Khaengkhan, Phirayot; Wanna , Ruchuon; Khaengkhan, Parinda (Kalasin University Journal of Science Technology and Innovation, 2025)
This research aimed to study the efficacy of plant extracts, including neem seeds, marigold flowers, and sweet flag rhizomes, in controlling the lesser grain borer (Rhyzopertha dominica (Fabricius)) in seed storage, as well as their effects on rice seed quality. Experimental design followed factorial in CRD with four replications. Plant extracts were analyzed for their chemical composition using Gas Chromatography-Mass Spectrometry (GC-MS). Chemical analysis revealed that the main compound in neem seed extract was trans-13-octadecenoic acid (31.89%), in marigold flower extract was α-tocopherol (11.49%), and in sweet flag rhizome extract was asarone (39.94%). Repellent contact test showed that sweet flag extract had the highest efficacy, repelling 93.92% of lesser grain borers within an hour at 40% concentration, and maintaining its effectiveness throughout the experiment. Insecticidal contact test found that neem and sweet flag extracts at 40% concentration resulted in 100% mortality of lesser grain borers within an hour. The study on preventing infestation in stored rice seeds revealed that woven plastic sacks treated with sweet flag extract provided the highest protection, preventing 93% on the first day of the experiment and maintaining effectiveness for two weeks. The study on the effects of sweet flag extract on rice seed germination showed that woven plastic and gunny sacks treated with the extract had no negative impact on seed germination, with the highest germination rate reaching 96.25% in the fourth week. The research findings indicated that sweet flag has high potential as a natural insect control agent and could be applied for rice seed storage.